Dental caries bacterial isolates sensitivity toward water-, ethanolicextract and essential oils of several shallot cultivars (Allium cepa) - IDA INDRAWATI; AULIA PONNY ANGGRAINI; BUDI IRAWAN (Smujo International, 2017)
Indrawati I, Anggraini AP, Irawan B. 2017. Dental caries bacterial isolates sensitivity toward water-, ethanolic- extract and essential oils of several shallot cultivars (Allium cepa). Nusantara Bioscience 9: 229-235. Sensitivity test of dental caries bacterial isolates has been carried out toward water-, ethanolic- extract and essential oil of Batu, Maja, Sumenep shallot cultivars. The experimental method was conducted using sensitivity test through Kirby-Bauer method with randomized complete design factorial 5 x 16 for each shallot cultivars with two replications. Factor one (i) was dental caries bacteria isolates (Lactobacillus sp., Staphylococcus sp.1, Staphylococcus sp.2, Staphylococcus sp.3 and Streptococcus sp.). The other factor (ii) was an antibacterial agent (water-extract, ethanolic- extract and essential oil of Batu, Maja, Sumenep shallot cultivars and antibiotic Vancomycine 30 Î¼g). Concentration for each shallot cultivars extract that used was 80%, 40%, 20%, 10% and 0%. The result of sensitivity test to those antibacterial agents showed that 80% water extract of Maja cultivar had the best inhibition zone of Staphylococcus sp.1 growth with the average of inhibition zone 37 mm. The interaction factor between essential oil from Batu and Maja as well as Sumenep shallot cultivar revealed a better inhibition zone than Vancomycine 30 Î¼g with all bacterial isolates tested.